An ASP.NET website for nurse - Yang, Guang (2015)
As the world technical improved, almost everything will be recorded on the internet. Hospital medical information is an important part of our daily life. To keep update all information of our medical records to the internet can help on our future treatments. Due to the records doctors can use those records as reference to decide what kind of treatment will be given and what should be avoid. Patient can also go to the nearest clinic for the sequential treatment instead of go back to the hospital which is waste time and medical resource. Due to these reasons, our medical information system is necessary and important. For the nurse system, nurse should find out all necessary information of patient and keep updating the daily inspection for patient. Those data can help on doctor’s analysis of patient’s situation and direct the usage of medicine.